The Repression of Resistance in Tripolitania Through the Documents by the Special Court for the Defense of the State: Ongoing Research (Italian Review of Legal History, 2020)
The aim of this brief work is to indicate the fundamental features of an ongoing research on the judgements issued from 1927 to 1939 by the Special Court forthe Defense of the State in Tripolitania preserved at the Central State Archive. While it is now quite clear which were the methods of repression implemented by the SCDS in Italy, its activity in Africa, its aims and the limits of its capacity to intervene, are still to be explored.However, after a quick survey of the archival material, it is clear that the examination of the judgements of this court implies a deeper insight into the complex colonial reality, characterized by ethnic fragmentation, religious and cultural events that are reflected in the twenty-year events of the Libyan resistance against the Italians.These fragmentations have not only made uneven and often sterile the intervention of the colonizers, who were first “liberal” and then “fascist”, but they also determined, after the conquest of the independence of the African state in 1951, a substantial lack of dialogue between European and African historiographies.For this reason, the historiography on Libya is certainly rich, but pays the consequences of a difficult communication due to the deep cultural differences, starting from the Arabic language, which have made difficult the dialogue between Italian and Libyan historians in the last decades of the last century.We will try here to give an account of what emerged from an initial bibliographical survey that has for purpose of understanding the SCDS judicial activity in the colony. In particular, what we want to understand is who was the enemy that the fascists tried to fight with their court of political justice, what tools they faced it with, how great was the distance between the real enemy (as much as it is possible for us to understand it) and the enemy created by the lack of understanding and by the propaganda of the Metropolis. For this purpose our work is organized around two poles: the colonizers and the colonized.
Keywords: Special Court for the Defense of the State (SCDS); Libya; National Central Archives; colonies; Fascism; political justice.